Interesting record of the representative of genus Stigonema С.Agardh ex Bornet et Flahault (Stigonemataceae, Nostocales, Cyanobacteria) in the Podilsky Tovtry National Nature Park (Khmelnytski Region, Ukraine) - Vinogradova, O.M.; Nyporko, S.O.; Kozyr, M.S. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2023)
The paper deals with first record of the representative of the nostocalean genus Stigonema in the terrestrial ecotope in the Forest-Steppe Zone of Ukraine. It was revealed in Cladonia dominated cryptogamic soil crust sampled from limestone outcrops with a rock-oak-hornbeam forest on the high bank of the Dniester Reservoir (Podilskyi Tovtry NNP). Heterocytous cyanobacterium with true branching identified as Stigonema minutum Hassal ex Bornet et Flahault formed prostrate blackish felty films on the surface of the crust. Information on morphological and dimensional features of the studied population, photomicrographs of natural material, characteristics of the habitat are given. Data on the distribution of the species within Ukraine, as well as ecological and biogeographic features of S. minutum are discussed.